Australian quad bike fatalities: what is the economic cost?. (2nd April 2013) - Lower, Tony; Pollock, Kirrily; Herde, Emily
Abstract Objective : To determine the economic costs associated with all quad bike‐related fatalities in Australia, 2001 to 2010. Methods : A human capital approach to establish the economic costs of quad bike related fatalities to the Australian economy. The model included estimates on loss of earnings due to premature death and direct costs based on coronial records for ambulance, police, hospital, premature funeral, coronial and work safety authority investigation, and death compensation costs. All costs were calculated to 2010 dollars. Results : The estimated total economic cost associated with quad bike fatalities over this period was 288.1 million, with an average cost for each fatality of 2.3 million. When assessing the average cost of incidents between age cohorts, those aged 25–34 years had the lowest number of fatalities but had the highest average cost (4.2 million). Conclusions : Quad bike fatalities have a significant economic impact on Australian society that is increasing. Implications : Given the high cost to society, interventions to address quad bike fatalities have the potential to be highly cost‐effective. Such interventions should focus on design approaches to improve the safety of quad bikes in terms of stability and protection in the event of a rollover. Additionally, relevant policy (e.g. no children under 16 years riding quads, no passengers) and intervention approaches (e.g. training and use of helmets) must also support the design modifications.